QoS-based resource management and optimization in CR-based NOMA networks - Akyol, Ömer Faruk (Graduate School, 2023)
The improvement of spectral efficiency (SE) and energy efficiency (EE) is crucial for the development of mobile communication networks. Non-orthogonal multiple access (NOMA) technique has been presented as an effective method to improve SE and EE of wireless communication systems. Also, cognitive radio (CR) is important to improve SE and EE in these systems in addition to NOMA. The collaboration between NOMA and CR possesses the capacity to tackle the issue of spectrum scarcity by facilitating the utilization of a shared frequency band by numerous users. The collaboration between NOMA and CR can optimize EE by reducing power consumption in wireless communication devices. Also, integrating the simultaneous wireless information and power transfer (SWIPT) technique with the CR-based NOMA (CR-NOMA) scheme can present a viable solution to effectively tackle the issue of limited spectrum resources and energy scarcity in wireless communication networks. The CR-NOMA enables multiple users to access a typical frequency band by utilizing non-orthogonal resource allocation techniques. With SWIPT, energy-limited devices can harvest energy from the received signals while decoding the information. The thesis study examines the performance of this CR-NOMA combination in three different scenarios. In the first and second parts of the thesis work, two different CR-NOMA-based networks without SWIPT are discussed. The first of these networks considers a multi-antenna CR-NOMA system, especially for sub-6 GHz frequencies. The second of these networks represents a beamforming assisted- multi-antenna CR-NOMA system, especially for Millimeter wave (mmWave) frequency bands. After that, a CR-NOMA-based network with SWIPT is considered in the three parts of the thesis work. An essential challenge associated with the implementation of CR-NOMA pertains to the imperative need to guarantee the Quality of Service (QoS) requirements for all users operating in parallel, along with enhancing the SE of the CR-NOMA framework. In the initial part, this challenge assumes a paramount significance in CR-NOMA scenarios where multiple users share a frequency band, as the presence of interferences amongst users can result in a decline in the overall performance of communication networks. The effectiveness of Successive Interference Cancellation (SIC) in decoding the received signal is of critical importance in reducing the Outage Probability (OP) of CR-NOMA networks that cater to both Primary Users (PUs) and Secondary Users (SUs), utilizing a common frequency resource block. This part discusses a CR-NOMA system featuring multiple antennas and multiple users, which is designed for uplink communication. The current system evaluates the QoS requirements of users and scrutinizes the effect of SIC on the occurrence of the outage. A key importance of this chapter lies in addressing the obstacles associated with QoS-based SIC in NOMA networks using CR technology and multiple antennas. Hence, the thesis aims to enhance the outage performance of the entire network and satisfy the QoS requirements for PUs and SUs in CR-NOMA networks by implementing novel user pairing strategies. This study puts forward two novel antenna and SU selection algorithms, with the objective of enabling efficient allocation of both PUs and SUs within the system. The primary aim is to enhance the outage performance and diminish the impact of the error floor while accommodating the QoS requirements of both PUs and SUs. The present study demonstrates that the multi-antenna CR-NOMA system, in conjunction with QoS-based SIC algorithms, yields superior performance compared to the conventional channel state information (CSI)-based SIC technique. This notable enhancement in system performance is attributed to the effective management of interference and pairing of users facilitated by the QoS-based SIC algorithms. The thesis presents a formalized expression of the OP that is derived for the proposed suboptimal antenna and SU selection algorithm, represented in a closed form. Furthermore, the thesis represents the mathematical expression for the OP of this system equipped with a single antenna while the suggested algorithms are not employed. Theoretical analyses are verified through extensive simulation results. The outcomes and implications of the thesis can provide a solid basis for subsequent inquiries and advancements in the design and enhancement of QoS-based SIC algorithms and user pairing strategies of CR-NOMA networks, taking into account, especially with scenarios multi-antenna. The advantages of this first part are further suitable for enhancing the SE in CR-NOMA networks employing sub-6 GHz frequencies especially. Hence, the need for different algorithms and system designs for enhancing the SE in CR-NOMA networks employing high frequencies as in mmWave communication. In the second part, the thesis presents the coexistence of two promising technologies for 5G and beyond mobile networks, namely CR-NOMA and mmWave wireless communication, to overcome the spectrum scarcity problem and enhance SE and EE. However, using mmWave bands in CR-NOMA networks can also present challenges. One of the most critical challenges is the increased susceptibility to blockages and path loss due to the high frequency of mmWave signals, resulting in unstable channel conditions and lower overall network performance. Also, beamforming in CR-NOMA networks can lead to increased interference between PUs and SUs, which can degrade the QoS for both user groups. The need for novel user pairing algorithms and suitable beamforming designs in mmWave CR-NOMA networks to ensure efficient and reliable communication exists. Hence, the thesis proposes a CR-NOMA user pairing algorithm for an uplink mmWave CR-NOMA network with a multi-antenna beamforming assisted-base station. In this network, an appropriate beamforming design is utilized to satisfy the QoS requirements of the PU. Also, this algorithm has been developed with the primary objective of maximizing the coverage probability by strategically selecting a SU to ensure the QoS requirements of both PU and SU are met through QoS-based SIC. Otherwise, the CSI-based SIC is performed over the SU, possessing the highest channel gain. The findings of Monte Carlo simulation experiments illustrate that the suggested algorithm presents an optimal coverage probability at reduced complexity, particularly in high signal-to-noise ratio (SNR) contexts. In the third section of this thesis, a hybrid approach integrating SWIPT and CR-NOMA is presented with the objective of enhancing both the SE and EE of wireless communication networks. However, the integration of SWIPT with CR-NOMA presents several noteworthy challenges. Designing energy harvesting protocols that effectively balance the tradeoff between energy harvesting and information decoding represents a critical challenge. The complexity of utilizing energy harvested at relay nodes for information processing and transmission poses a challenge in devising optimal power allocation strategies that guarantee QoS requirements while maintaining the EE. A downlink SWIPT-enabled CR-NOMA network with multiple energy-limited relay nodes under Nakagami-$m$ fading is considered in this part of the thesis. This thesis examines two fundamental energy harvesting protocols, specifically the time switching-based relaying (TSR) protocol and the power splitting-based relaying (PSR) protocol, for energy harvesting and information processing at the relay node. The primary aim is to minimize the OP while simultaneously maximizing the EE of the system. This thesis ensures an analysis of the impact of various design parameters, including the data rate target, the distance among nodes, the power coefficient allocated to users, and the transmission power, on the optimal ratio of PS and TS. It has been observed that the PS ratio demonstrates greater stable and constrained variation when contrasted with the TS ratio. Additionally, the thesis demonstrates that the utilization of the optimal PS ratio outperforms the optimal TS ratio concerning outage performance and EE within the suggested network. This thesis presents closed-form expressions for the OP and EE of the proposed system. %The thesis consists of 6 chapters. The first chapter of the thesis provides a comprehensive literature review of the CR-NOMA concept, including various subtopics such as CR-NOMA with QoS-based SIC, user pairing and beamforming design in mmWave CR-NOMA networks, and energy harvesting in multi-antenna CR-NOMA dual-hop relaying networks. Then, the chapter presents the motivation and contribution of the thesis. In Chapter 2, the various wireless communication technologies, which are used in the thesis, such as cooperative relaying, multi-antenna networks, and CR-NOMA communication, are introduced. In Chapter 3, the CR-NOMA system model is presented and this system is briefly investigated over the CSI-based SIC. After that, the same system model is investigated over the QoS-based SIC in detail and two user and antenna selection algorithms are proposed to increase the outage performance of the QoS-Based SIC in this system. Following that, the numerical and simulation results of this CR-NOMA system with these algorithms are discussed. In Chapter 4, an uplink mmWave CR-NOMA system model, including the CSI-based SIC, the QoS-based SIC, and the JSUS algorithm utilizing both SIC procedures, is presented. The Monte Carlo simulation experiments and results are provided over this system model. In Chapter 5, the SWIPT-enabled CR-NOMA network is proposed and the proposed network is investigated by using PSR and TSR, respectively. After that, the expression of OP and EE for the proposed system is obtained. The numerical and simulation results are given over this proposed CR-NOMA network. Finally, Chapter 6 contains a general conclusion about the results obtained in this thesis. As a result, The proliferation of wireless communication devices and data traffic has posed a considerable challenge due to the limited available spectrum. To overcome this challenge, the implementation of NOMA and CR techniques can present a viable solution to enable the concurrent utilization of frequency bands by multiple users while ensuring optimal utilization of the spectrum. The thesis work discusses the challenges and potential solutions in CR-NOMA networks in various scenarios to achieve a high SE and EE in CR-NOMA networks. In this way, the thesis work contributes to the understanding of the performance of CR-NOMA networks over three different scenarios. The algorithms and system designs presented in the thesis make a significant contribution to the comprehension of the performance of CR-NOMA networks, and offer viable strategies for addressing the obstacles encountered when incorporating dissimilar communication technologies including SWIPT, mmWave bands, and beamforming. The results of the present investigation suggest that the proposed algorithms and system designs possess the capability to significantly improve the SE and EE of CR-NOMA networks while simultaneously guaranteeing QoS requirements for users.
CR tabanlı NOMA ağlarında QoS tabanlı kaynak yönetimi ve optimizasyonu
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: mobil iletişim; mobile communication; networks; ağlar